Effect of Qiangdi 863 Nanosynergids Treated Water, Nitrogen, Phosphorous and Potassium Fertilizers on Rice Growth Physiology and Grain Quality - Younas, Afifa; Yousaf, Zubaida; Riaz, Nadia; Rashid, Madiha; Aftab, Arusa; Fiaz, Sajid; Shamsheer, Bushra; Huang, Shiwen (Frontiers in Plant Science, 2022)
In Asia, rice (Oryza sativa L.) is cultivated and consumed on large scale. However, abiotic stress in the form of temperature variation proved to be limiting factor for rice production. Rice is among the major staple food crops therefore, increasing rice productions could be a better solution to solve or at least decrease severity of global food crisis. In present ear, Nanotechnology is proving an emerging technique to solve the agricultural issues related to enhance productivity. Therefore, it is hypothesized that nano synergid like Qiangdi 863 biological assisted growth apparatus could enhance the germination, early growth rice physiology and yield of rice. The field experiment for this study was randomized completely block design (RCBD) to check the effect of nano-synergid 863 on early growth, yield and pest management. Experiment was consecutively performed for 3 years (2017-2019). The NTW significantly improved Speed of Germination (25.3 %, 35.6% and 32.3%), Final Emergence Percentage (100%) and Seed Emergence Energy Percentage (80%, 95% and 90%), radical (1.25cm, 1.7cm, 2.35cm) and pulmule growth (1.29cm, 1.24cm and 1.66cm), Soil Plant analysis development (46, 45 and 47), antioxidant enzymatic activities e.g. Catalase activity (34376 µg-1FW h-1 , 33264 µg-1FW h-1 and 34453 µg-1FW h-1), Superoxide Dismutase (18456 µg-1FW h-1,19445µg-1FW h-1 and 19954 µg-1FW h-1) Peroxide (745Ug-1FW, 734Ug-1FW and 752Ug-1FW) production and declined Malondialdehyde (4.5µmolg-1FW, 5.1µmolg-1FW and 4.2µmolg-1FW) for 2017, 18 and 19 years respectively in KSK 133. The application of nano-treated irrigated water enriched the bio-mass of rice seedlings. The overall nano synergid treatments successfully enhanced the endogenous hormones e.g. Salicylic acid (6016.27pmol/L, 5823.22pmol/L and 5922.12pmol/L), Jasmonates (5175.6pmol/L, 4231pmol/L and 5014.21pmol/L) Brassinosteroids (618.2pmol/L, 546.83pmol/L and 582.1pmol/L) quantification and yield 1000 grain weight (22.3g, 22g and 23.2g) of KSK 133. The results proved that NTW could effectively enhance early growth and yield of rice varieties